ANALISA PERBANDINGAN BIAYA MENGGUNAKAN METODE SNI DAN METODE BOW BESERTA PERHITUNGAN WAKTU DAN IDENTIFIKASI SDM, MUTU, K3 PADA GEDUNG KANTOR GRAHA UMKM DI KOTA PONTIANAK: COST COMPARISON ANALYSIS USING SNI AND BOW AND TIME CALCULATION AND IDENTIFICATION SDM, QUALITY, K3 METHODS IN BUILDING GRAHA UMKM OFFICE IN PONTIANAK CITY - Buih, de Kamilla; Rianto, Siswo; Arianti, iin (RETENSI, 2020)
The analysis is a detailed observation on the work by describing the constituent components for further study which is the meaning of. The thing that is needed in analyzing, of course, is making cost calculations using the SNI and BOW methods, calculating time, identifying occupational safety and health, identifying workers, identifying the quality of workbased on data planning and implementation.